Collaborative learning in radiography education. - Dowd SB (Radiologic Technology)
Collaborative learning is a collective term used to describe a variety of techniques in which the facilitator and the student explore problem-solving as a means of education. This article presents an overview of collaborative learning, including problem-based learning, a technique often used in medical schools. The article also discusses the foundations of collaborative learning and reviews the use of learning contracts in radiography education.